The American military a narrative history - Lookingbill, Brad D. 1969- (John Wiley/Blackwell, 2013)
The American Military: A Narrative History presents a comprehensive introduction to more than four centuries of American military history. Presents a chronological account of American military history from clashes between militias and Native Americans to 21st-century operations in Afghanistan and Iraq Features personal vignettes to put a human face on armed conflict. Addresses patterns of national service, the evolution of civil-military relations, and the advent of all-volunteer forces Puts events in historical context, and considers cultural, social, political, economic, and technological devel.